Solve Systems by Substitution

y = -2 4x - 3y = 18 Substitute the appropriate expression into theother equation of this system. 4x-3( ) = 18 ( The first step is shown. Solve the system of equations by substitution. y = -2 4x - 3y = 18 4x - 3(-2) = 18 , ) 2( ) -3y= -1 Substitute the appropriate expression into theother equation of this system. 2x - 3y = -1 x = y + 1 ( The first step is shown. Solve the system of equations using substitution. 2(y + 1) - 3y= -1 2x - 3y = -1 x = y + 1 , ) Substitute the appropriate expression into theother equation of this system. -2x-3( )=-7 y = 6x - 11 -2x - 3y = -7 ( The first step is shown. -2x - 3(6x - 11) = -7 Solve the system of equations using substitution. y = 6x - 11 -2x - 3y = -7 , ) 6x-5( ) = 12 y = -2x + 20 6x - 5y = 12 Substitute the appropriate expression into theother equation of this system. ( The first step is shown. y = -2x + 20 6x - 5y = 12 6x - 5(-2x + 20) = 12 Solve the system of equations using substitution. , ) -3( ) - 3y = -15 Substitute the appropriate expression into theother equation of this system. x = -3y + 1 -3x - 3y = -15 ( -3(-3y + 1) - 3y = -15 The first step is shown. Solve the system of equations using substitution. x = -3y + 1 -3x - 3y = -15 , ) |

Students who took this test also took :

Created with That Quiz —
a math test site for students of all grade levels.